Fluid flow in tumescent subcutaneous tissue observed with 3D scanning: massage accelerates injection dispersal. (17th May 2018) - Koulakis, John P; Dubrovsky, Genia; Huynh, Nhan; Rouch, Joshua; Dunn, James C Y; Putterman, Seth
Abstract: Objective: Tumescent injections are used for regional anesthesia, lipoplasty, and antibiotic delivery amonst others. We evaluate the potential of 3D scanning to monitor the extent and dispersal of tumescent injections and compare it to a method based on CT. We use the scanning technique to determine whether massage and/or transcutaneous ultrasound accelerates the dispersal of the tumescent fluid. Methods: 10–20 mL tumescent injections into live pig subcutaneous tissue were monitored with 3D scanning or CT and their response to waiting, massaging, or applying therapeutic ultrasound at 1 MHz and 3 W cm −2 was quantified. In a separate experiment, antibiotic was added to the tumescent fluid and serial blood samples were taken to monitor serum antibiotic concentrations. Massage or ultrasound was applied to generate a change in serum levels. Results: Massage significantly accelerates dispersal when compared to waiting ( p  < 0.05). Simultaneous application of ultrasound does not accelerate dispersal further. No change in serum antibiotic levels could be detected in response to massage or ultrasound. Conclusion: 3D scanning is an effective and inexpensive method of monitoring tumescent injections through the swollen skin profile. Although 3D scans do not capture the subcutaneous information revealed by CT, they do not require radiation or dedicated facilities.